BREAKFAST CULTURE FOR MENTAL SUSTAINABILITY OF 3RD SEMESTER STUDENTS IN KOTA PALANGKA RAYA - Yola Pradita; Cicha Widia, Matthew Timothy Palit, Santia Oktaviani, Linta, Maria Veronica, Reynhard Malau (CV. ADIBA AISHA AMIRA, 2023)
Breakfast for a student is very important, because our bodies require quite a lot of energy and calories. By having breakfast, the brain will feel fresher and can function well, because the impact of not eating breakfast is a decrease in students' thinking and learning abilities. Breakfast is beneficial for every human being to maintain endurance, maintain physical endurance and be able to increase work productivity. In the body there is glucose which functions as the main energy source for the brain. Because nowadays it is very rare for students to eat breakfast, perhaps because of laziness or various kinds of busyness which makes them forget to have breakfast. However, breakfast is very beneficial for the body and health, especially for students so they can focus on studying.